DAMPAK IMPLEMENTASI PARIWISATA HALAL TERHADAP DINAMIKA PERTUMBUHAN EKONOMI REGIONAL DI PROVINSI BANTEN - Dadang Hermawan; Dendi Riswandi; Mumu Zainal Mutaqin (Universitas Mathla’ul Anwar Banten, 2026)
This study aims to analyze in depth the impact of halal tourism implementation on regional economic growth dynamics in the rich province of Banten, which has great opportunities to utilize halal tourism as a new catalyst for sustainable economic growth. It also seeks to identify how the development of a halal tourism ecosystem, which includes the provision of facilities and services in accordance with sharia principles, can increase the number of tourist visits and encourage investment in related sectors. The research method used is qualitative with a literature study type. This approach was chosen to comprehensively collect, review, and analyze various secondary data sources, such as previous research reports, scientific journals, official local government publications, and policies related to halal tourism and the regional economy in Indonesia, particularly in Banten Province. Through a literature study, researchers can map relevant concepts, theories, and empirical findings to build a strong analytical framework and identify patterns, trends, and gaps in the discussion of the contribution of the halal tourism sector to indicators of regional economic growth in Banten. The results of the discussion show that the implementation of halal tourism in Banten Province has had a positive and significant impact on accelerating regional economic growth. This strategy has succeeded in expanding the target market to domestic and global Muslim tourists who are sensitive to sharia aspects, which has led to an increase in foreign exchange and money circulation in the region. Furthermore, the development of halal tourism has clearly boosted the local economy, especially in the micro, small, and medium enterprises sector engaged in halal culinary, Muslim fashion, and handicraft products. This indicates that halal tourism not only increases revenue in the tourism sector but also drives diversification and resilience in the overall regional economy of Banten.